2001
DOI: 10.1177/00912700122012797
|View full text |Cite
|
Sign up to set email alerts
|

Onset of Analgesia for Liquigel Ibuprofen 400 mg, Acetaminophen 1000 mg, Ketoprofen 25 mg, and Placebo in the Treatment of Postoperative Dental Pain

Abstract: Ibuprofen is a peripherally acting nonsteroidal anti-inflammatory drug indicated fo ranalgesia, antipyresis, and various arthritic conditions. A solubilized 200 mg liquigel formulation of ibuprofen has been shown to have a more rapid rate of absorption compared with ibuprofen 200 mg tablets. Ibuprofen liquigels have a kinetic profile similar to ibuprofen suspension, with both a higher Cmax and an earlier tmax than any solid tablet. The objective of this single-dose, double-blind, triple-dummy, parallel-group s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 11 publications
2
54
0
3
Order By: Relevance
“…Measures of analgesic duration-the proportion of patients taking rescue medication and the time to rescue medication-showed that those in the acetaminophen group received rescue medication sooner than those in either of the two ibuprofen groups. This suggests that both ibuprofen formulations had a longer duration of action than acetaminophen, which is in keeping with that previously reported for ibuprofen lysine [22] and ibuprofen liquigel [23]. In terms of pain relief and PID, the timepoint at which a significant difference was first observed between either of the ibuprofen formulations and placebo was 15 min (sodium ibuprofen); a significant difference between either of the ibuprofen formulations and acetaminophen was first observed at 45 min (sodium ibuprofen).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Measures of analgesic duration-the proportion of patients taking rescue medication and the time to rescue medication-showed that those in the acetaminophen group received rescue medication sooner than those in either of the two ibuprofen groups. This suggests that both ibuprofen formulations had a longer duration of action than acetaminophen, which is in keeping with that previously reported for ibuprofen lysine [22] and ibuprofen liquigel [23]. In terms of pain relief and PID, the timepoint at which a significant difference was first observed between either of the ibuprofen formulations and placebo was 15 min (sodium ibuprofen); a significant difference between either of the ibuprofen formulations and acetaminophen was first observed at 45 min (sodium ibuprofen).…”
Section: Discussionsupporting
confidence: 91%
“…In terms of pain relief and PID, the timepoint at which a significant difference was first observed between either of the ibuprofen formulations and placebo was 15 min (sodium ibuprofen); a significant difference between either of the ibuprofen formulations and acetaminophen was first observed at 45 min (sodium ibuprofen). In comparison with previously published data, studies with ibuprofen arginate and ibuprofen lysine demonstrated significant differences in pain relief and PID between ibuprofen and placebo at 10-15 min [11,12,19,23]. Furthermore, significant differences between ibuprofen lysine and acetaminophen were observed at 15 min, much sooner than the 45 min observed in our study [22].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Ibuprofen lysine 400 mg produces faster onset and higher peak analgesia than a conventional tablet of ibuprofen acid 400 mg in dental pain. 29 Solubilized liquigel ibuprofen 400 mg had more rapid onset than acetaminophen 1000 mg and had a longer duration of action than either acetaminophen 1000 mg or ketoprofen 25 mg. 30 These differences can be clinically important as the median time to clinically meaningful relief of pain was shorter after solubilized ibuprofen 400 mg than after acetaminophen 1000 mg. 31 The solubilized potassium liquigel formulation of ibuprofen is available over-the-counter worldwide. Diclofenac sodium softgel has also been shown to provide a very rapid onset of analgesic activity and prolonged analgesic duration compared with conventional diclofenac potassium.…”
Section: Effects Of Formulation On the Analgesic Activity Of Nsaidsmentioning
confidence: 99%
“…53 The DERP reviews are updated at least annually, and are subject to peer review and public comment before final publication. 54 These sources were sufficient for evaluating most claims, but for six claims, the coders were provided with additional references: publications from head-to-head trials comparing acetaminophen to ibuprofen, [55][56][57][58][59][60][61] IMS Health data from 2008 to evaluate a claim of prescription popularity, 62 nonprescription label information for a discontinued product from an archived web page, 63,64 links to specific nonprescription drug product labels to evaluate the incipient ingredients in the product, 65,66 and a press release providing up-to-date information to support an advertising claim. 67 We only used publicly available evidence to evaluate claims and did not make requests to pharmaceutical companies for unpublished or "on-file" evidence.…”
Section: Coding: Evaluating the Truthfulness Of The Major Claimmentioning
confidence: 99%